The Influence of Perceived Ease of Use and Perceived Benefits on the Interest in Using Shopeepay Among Accounting Education Students at Muhammadiyah University Surakarta - Muhammad Adi Krisnanto; Dhany Efita Sari (International Journal of Business Studies, 2025)
This study aims to examine the influence of perceived ease of use and perceived usefulness on the interest in using Shopeepay among accounting education students. This study uses a quantitative approach with a comparative causal design. The study population consists of students of the Accounting Education Study Program at the Faculty of Teacher Education and Training, Muhammadiyah University Surakarta, who use ShopeePay. This study used a sample size of 111 student respondents. The sample was obtained using random sampling techniques. The tool used in this study was a questionnaire distributed through Google Forms. The findings of this study indicate that both the simultaneous F test, regression coefficient, and partial t-test show that the perception of ease of use has a negative and insignificant effect on the interest in using ShopeePay, while the perception of benefits has a positive and significant effect on the interest in using ShopeePay. Both variables together have a significant influence on the interest in using ShopeePay, contributing 63.5% to that interest. The data shows that service benefits are the main method of generating interest in using ShopeePay.